2020
DOI: 10.3390/genes11020137
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Geno- and Phenotyping in a Complex Pedigree Including Four Different Inherited Retinal Dystrophies

Abstract: Inherited retinal dystrophies (IRDs) are characterized by high clinical and genetic heterogeneity. A precise characterization is desirable for diagnosis and has impact on prognosis, patient counseling, and potential therapeutic options. Here, we demonstrate the effectiveness of the combination of in-depth retinal phenotyping and molecular genetic testing in complex pedigrees with different IRDs. Four affected Caucasians and two unaffected relatives were characterized including multimodal retinal imaging, funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Similarly, in a US study, involving three IRD pedigrees, each given an initial diagnosis of RP, one with a dominant RP and the other two with a dominant, incompletely penetrant RP, it was found that multiple IRD genes were responsible for various affected individuals in each of the three families: both USH2A and RP1 was segregating in one family; PRPH2 and CRX in a second family and PRPH2 , PRPH8 and USH2A in the third family [ 85 ]. These studies, however, are trumped in complexity by Birtel et al’s analysis of a single family with four different IRDs each caused by distinct pathogenic variants and inheritance patterns: father, RHO , dominant RP; mother, ABCA4 and CACNA1F , recessive Stargardt and CSNB; first son, CACNA1F , CSNB; second son, MITF , dominant Waardenburg syndrome [ 86 ]. These are some examples of the many that exist, illustrating the complexity of IRD screening and reinforcing the necessity of thorough clinical and genetic investigation prior to genetic counselling [ 87 ].…”
Section: Irds—target Panels and Whole Exome Studiesmentioning
confidence: 99%
“…Similarly, in a US study, involving three IRD pedigrees, each given an initial diagnosis of RP, one with a dominant RP and the other two with a dominant, incompletely penetrant RP, it was found that multiple IRD genes were responsible for various affected individuals in each of the three families: both USH2A and RP1 was segregating in one family; PRPH2 and CRX in a second family and PRPH2 , PRPH8 and USH2A in the third family [ 85 ]. These studies, however, are trumped in complexity by Birtel et al’s analysis of a single family with four different IRDs each caused by distinct pathogenic variants and inheritance patterns: father, RHO , dominant RP; mother, ABCA4 and CACNA1F , recessive Stargardt and CSNB; first son, CACNA1F , CSNB; second son, MITF , dominant Waardenburg syndrome [ 86 ]. These are some examples of the many that exist, illustrating the complexity of IRD screening and reinforcing the necessity of thorough clinical and genetic investigation prior to genetic counselling [ 87 ].…”
Section: Irds—target Panels and Whole Exome Studiesmentioning
confidence: 99%
“…IRDs are clinically and genetically heterogeneous diseases, and the early accurate diagnosis is difficult to achieve. Birtel et al reported one pedigree with four IRDs in which the diagnosis was confirmed by combining in‐depth retinal phenotyping and molecular genetic testing (Birtel et al, 2020). It is not rare for icCSNB patients to be misdiagnosed with other eye conditions before genetic testing (Men et al, 2017; Pasutto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, it would be assumed that multiple members of a family affected with retinal degeneration would have the same genetic cause of disease. However, there have been reports of more than one genetic cause of retinal degeneration being identified within a family (Birtel et al, 2020; Jones et al, 2017). This situation can complicate inheritance counseling and selection of the appropriate genetic test for individuals in these families.…”
Section: Complications That Can Emerge When Ordering Genetic Testingmentioning
confidence: 99%